2019
DOI: 10.3389/fmicb.2019.00985
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Resistance in Salmonella Typhimurium Isolates Recovered From the Food Chain Through National Antimicrobial Resistance Monitoring System Between 1996 and 2016

Abstract: Salmonella is a major foodborne pathogen which causes widespread contamination and infection worldwide. Salmonella Typhimurium is one of the leading serovars responsible for human and animal salmonellosis, globally. The increasing rate of antibiotic resistance in Salmonella Typhimurium poses a significant global concern, and an improved understanding of the distribution of antibiotic resistance patterns in Salmonella Typhimurium is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
164
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(177 citation statements)
references
References 66 publications
12
164
1
Order By: Relevance
“…All (80) Salmonella isolates were found multidrug-resistant. In agreement with this study Salmonella were developed multidrug resistance in Modjo [18], Gondar [7], Jimma [9], and China [8]. This multidrug resistance might be due to the irrational use of antibiotics practiced in the area [26,27] and or evolutionary nature of Salmonella species [16].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…All (80) Salmonella isolates were found multidrug-resistant. In agreement with this study Salmonella were developed multidrug resistance in Modjo [18], Gondar [7], Jimma [9], and China [8]. This multidrug resistance might be due to the irrational use of antibiotics practiced in the area [26,27] and or evolutionary nature of Salmonella species [16].…”
Section: Discussionsupporting
confidence: 72%
“…Alimentarius are working against antibiotic resistance and set action plans to minimize antibiotic use along the food chain it is increasing at an alarming rate [13,14]. Before this research, many other types of research were conducted to assess the resistance pattern of Salmonella both in human and animals, but due to "evolutionary nature of the bacteria and the dependency of patients to antibiotics", the resistance level of Salmonellae to antibiotics are increasing from time to time [15,16,17,18,6,7,8,9]. Antibiotic resistance surveillance in food animal like sheep is strongly recommended for the mitigation of this global health crisis (AMR) and there was no surveillance has done yet in the study area.…”
Section: Even If the International Tripartite Organizations (Who Faomentioning
confidence: 99%
“…Nowadays, due to regulations on the use of antibiotics in poultry production derived from the problems of bacterial resistance, and considering that S. Typhimurium is a bacterium capable of developing antimicrobial resistance more quickly than other Salmonella species [12,13], several strategies have been proposed to treat and control Salmonella infections [14]. Despite the large number of alternatives that have been tried, it has been reported that the combination of polyphenolic compounds with metal ions, such as copper, can enhance their antioxidant, anti-in ammatory, and antimicrobial effects, with the additional advantage that the toxicity of metal ions is reduced by the formation of complexes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…S. Typhimurium can also cause life-threatening invasive diseases in immunocompromised individuals [32]. The intracellular environment and frequent multidrug resistance protect Salmonella enterica against extracellular antibiotics and facilitates disease relapse [33][34][35]. Thus, it is necessary to look for alternative ways to combat infections with this foodborne pathogen [36,37].…”
Section: Introductionmentioning
confidence: 99%